2019
DOI: 10.15694/mep.2019.000232.1
|View full text |Cite
|
Sign up to set email alerts
|

As you sow, so shall you reap: Is there a “golden standard” to teach histology?

Abstract: Finland (Kuopio, Finland) we implemented teaching methods with our medical and dental students that show effectiveness through objective and subjective measures. Our strategic vision and mission for education is summarized in Supplementary File 1. The question discussed below is: What teaching methods, systems, and approaches ensure the most effective knowledge transfer and class conditions for medical and dental graduates during histology education?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Our findings with regard to P (preferability) concur with the work of Felszeghy et al (2019) identifying the benefits of group-based gamification as opposed to individual gameplay. The new findings from this study provide insights into the relevance of such endeavors to the project-based and group-based nature of the summative assessment of the learning program and the learning context.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings with regard to P (preferability) concur with the work of Felszeghy et al (2019) identifying the benefits of group-based gamification as opposed to individual gameplay. The new findings from this study provide insights into the relevance of such endeavors to the project-based and group-based nature of the summative assessment of the learning program and the learning context.…”
Section: Discussionsupporting
confidence: 86%
“…helped students to revisit the key learning points of missed lectures, and significantly assisted them in knowledge reinforcement and retention (Tan et al, 2018). Felszeghy et al (2019), in a quantitative study on human morphology at a university in Finland, found positive results in students’ learning as a result of a gamification activity that increased the learner’s motivation and helped the leaner to overcome individual difficulties and develop collaborations with other learners. Gamification has promoted interest in and received positive feedback from senior professionals and learners (Felszeghy et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%